Students’ Perception Toward Learning Vocabulary by Using U-Dictionary Application at the First Grade Students of SMAN 3 Jambi in Academic Year 2020/2021 - Dwi Muslimawati; Kartika Dewi; Efa Silfia (JELT: Journal of English Language Teaching, 2021)
The purpose of the research is to know how the students’ perception toward learning vocabulary by using U-Dictionary application at the first grade students of SMAN 3 Jambi. This research is uses qualitative as the design of this research. The setting of this research is located at Jl. Guru Mukhtar Kota Jambi. The subject of the research is students in X science 1 with the total number 30 students but it takes 6 students in purposive sampling. The instrument of this research is used interview. Data were collected by using interview and analyzed by using code technique. Based on the results of interview all of the students prefer to use U-Dictionary application to learn vocabulary than the printed dictionaries. The use of U-Dictionary application had positive and negative effect for students such as students are easier to understand and more practical, the students can learning English form unknown become know, U-Dictionary application added some new words, it can made the students’ refresh, it can be used anytime and anywhere and suitable for current digital era. While negative effect such as, the students felt annoyed by many advertisements that appear on the U-Dictionary application, the students felt that sometimes in the conversation feature the students’ voice are not detected, and the students felt that when their handphone battery runs out then they are automatically cannot use the U-Dictionary application. Finally, more students stated positive perception than negative perception.Key words: Students’ perception, Vocabulary, U-Dictionary application